Food loss and waste in food services from educational institutions in Costa Rica - Brenes-Peralta, Laura Patricia (2021)
One-third of the worldwide food production is lost or wasted, generating impacts in the food systems. However, data indicates that one in nine people suffer from undernourishment or shortage of food in the world. Furthermore, this problem generates adverse impacts in the environment and the economy. Costa Rica is not exempt from this phenomenon; therefore, in compliance with target 12.3 of the Sustainable Development Goals, the country initiated actions through the Costa Rican Food Loss and Waste Reduction Network and one of its members, the Costa Rican Network of Sustainable Educational Institutions (REDIES). This latter committed itself to quantify the food loss and waste (FLW) in the canteens from a pilot group of their members. The objective of this case study was to determine the FLW in the restaurants of five institutions to generate data experience that allows to create indicators and useful information in the search for strategies against food waste. The amount of FLW was measured using the standardized methodology explained in the Guide for this purpose, published by the Costa Rican Network. In general terms, most FLW in this case study comes from the amount of food leftovers. Consequently, it is concluded and recommended to focus on awareness campaigns, quality and portioning to address the issue, and to consider that each institution must place emphasis through its reduction plan with respect to the findings generated in each food service or canteen.